Representation Of Liberal Feminism In Greta Gerwig's Little Women Movie - Salam, Amanda Riskia; Rullyanti, Merry; Sembiring, Lina Tri Astuty (UNIVED Press, 2025)
Abstract This study aims to analyze the portrayal of liberal feminism in Greta Gerwig's film